Closed-Chamber Anterior Capsulorhexis Under Air Tamponade In White Cataract - Alsmman AH (Dove Medical Press, 2019)
Alahmady H Alsmman, Amr Mounir, Khulood M Sayed, Engy M Mostafa Department of Ophthalmology, Faculty of Medicine, Sohag University, Sohag, EgyptCorrespondence: Amr MounirDepartment of Ophthalmology, Sohag Faculty of Medicine, Sohag University, Sohag 82524, EgyptTel +20 10 0502 6170Email dramrmonir@yahoo.comPurpose: To evaluate the efficacy and safety of a closed-chamber air bubble capsulotomy technique to prevent the Argentinean flag sign (AFS) in patients with white and intumescent cataracts.Setting: Sohag University, Faculty of Medicine, Ophthalmology Department, Sohag, Egypt.Design: Prospective interventional noncomparative case series.Methods: Eighty-two eyes of 80 patients with white and intumescent cataracts were included. Eyes with any ocular pathology other than cataract or eyes subjected to previous intraocular surgery were excluded. Needle capsulorhexis was performed under a large air bubble tamponade without capsular staining. Efficacy of the technique was assessed intraoperatively by successful completion of capsulorhexis. Safety of the technique was assessed by the occurrence of intraoperative or postoperative complications.Results: Complete capsulorhexis by the closed-chamber air bubble technique was successful in 75 eyes (91.5%), while capsulorhexis extension occurred in seven eyes. In four eyes with extension, the procedure was shifted to the standard technique of CCC (circular curvilinear capsulorhexis), using a viscoelastic device. A shift to extracapsular cataract extraction (ECCE) surgery occurred in the remaining three eyes, as the extension was so far-gone. No intraoperative or postoperative complications were observed.Conclusion: The closed anterior chamber air bubble technique for capsulorhexis is a novel, safe, and effective technique to prevent AFS in white and intumescent cataracts. It is also time-saving and cost-effective, with less likelihood of capsulorhexis extension. The technique is considered a valuable addition to previously described techniques.Keywords: air tamponade, white cataract, intumescent cataract, phacoemulsification, capsulorhexis